Medial elbow approaches for coronoid fractures: risk to the ulnar nerve - Olawale A. Sogbein, MD, MSc, FRCSC; Shav Rupasinghe, MBChB, FRACS; Yibo Li, MD, FRCSC; Yousif Atwan, MD, MSc, FRCSC; Armin Badre, MD, MSc, FRCSC; Thomas Goetz, MD, FRCSC; Graham J.W. King, MD, MSc, FRCSC (JSES International)
Background: Coronoid fractures often require open reduction internal fixation (ORIF) to restore elbow stability. The flexor pronator split, flexor carpi ulnaris (FCU) split, and Taylor and Scham (T&S) approaches are frequently used medial approaches to access the coronoid. The ulnar nerve can be released or transposed when performing these exposures. The optimal medial surgical approach and management of the ulnar nerve has not been clearly defined. The purpose of this study was to compare postoperative ulnar nerve complications in coronoid fractures undergoing ORIF following a medial surgical approach and ulnar nerve release or transposition. Methods: A retrospective review of 91 patients with coronoid fractures treated with ORIF using a medial approach from 2004 to 2022 was performed at three academic medical centers. Patients ≥ 18 years of age who sustained coronoid fractures with or without associated injuries were included. Patient charts and perioperative imaging were reviewed. Patient demographics, fracture classification, associated injuries, surgical approaches, ulnar nerve management, and postoperative complications were recorded. Primary outcomes assessed were signs and symptoms of postoperative ulnar nerve neuropathy. Results: The mean age of the cohort was 45 ± 16 years, 71% were males, with a mean length of follow-up of 16 ± 22 months. Of the 91 coronoid fractures, 69 were anteromedials, eight were tips, and 14 were basal types. The incidence of preoperative ulnar neuropathy was 5% (n = 5). The incidence of postoperative ulnar neuropathy was 33% (n = 30) of which 55% (n = 16) completely resolved by final follow-up. The rate of postoperative ulnar neuropathy was not significantly different between in situ release 30% (n = 9) or transposition of the ulnar nerve 34% (n = 20), (P = .64). There was a significantly higher rate of postoperative resolution with transposition (70%) versus in situ release (22%), (P = .045). The rate of postoperative ulnar neuropathy was not significantly different between the FCU, T&S, or flexor pronator split approaches, (P = .331). Finally, the rate of neuropathy resolution was not significantly different between medial approaches (P = .46). Conclusion: There was no statistical difference in the incidence of postoperative ulnar nerve complications with ulnar nerve transposition or in situ release following coronoid fixation. However, transposing the nerve resulted in a higher rate of neuropathy resolution. While the incidence of postoperative ulnar nerve dysfunction is high following coronoid fixation when using a medial surgical approach, it was similar with the FCU, T&S, and flexor pronator split approaches. Larger cohorts and randomized clinical trials are needed to confirm these findings.